2019
DOI: 10.22176/act18.3.200
|View full text |Cite
|
Sign up to set email alerts
|

(Re)centering Indigenous Perspectives in Music Education in Latin America

Abstract: Indigenous knowledge has been marginalized and excluded through a system based on a worldview that perpetuates colonialism. The actions and attitudes of nation-states and academic bodies deem, recognize, and value certain ways of knowing as "superior," which marginalizes knowledge from Indigenous cultures. Considering an educational philosophy that puts the knowledge and worldviews of local cultures at its heart is an urgent step towards changing this situation. In this text, I discuss the implementation of St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several studies analyzing curricular content and revision found that music curricular revision recentered teaching and content around student affordances and community music traditions. Moreover, the choice of music pieces, such as indigenous rather than non-indigenous selections, carries high potential to mobilize efforts toward cultural relevance, student responsiveness, community integration, and general decoloniality (Vázquez Córdoba, 2019).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Several studies analyzing curricular content and revision found that music curricular revision recentered teaching and content around student affordances and community music traditions. Moreover, the choice of music pieces, such as indigenous rather than non-indigenous selections, carries high potential to mobilize efforts toward cultural relevance, student responsiveness, community integration, and general decoloniality (Vázquez Córdoba, 2019).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Instead, Indigenous communities, as is the case of Masewal people, are complex and often hold conflicts and contradictions. To create idyllic representations of what Indigenous peoples must be and to simplify the struggles that they face in their everyday lives is yet another form of racism and discrimination (Vazquez-Cordoba, in press). As researchers, let us walk side by side with our community partners and let us do our best to open the necessary space for their stories and realities to be shared through their own lenses.…”
Section: Meaningful Relationships Of Collaboration In Research: Towar...mentioning
confidence: 99%
“…Vázquez Córdoba (2019) notes that the tangled web of Indigenous musical practices and society favor "the reproduction of culture through maintaining dialogue about its meaningful anchors like ways of doing, saying, and feeling" (209). The life flowing through Indigenous musical practices and culture is dynamic and participatory in contemporary contexts, evolving alongside its peoples and circumstances (Vázquez Córdoba 2019, 209, 215).…”
Section: Surveying Indigenous American Musical Practice and Western A...mentioning
confidence: 99%